2010
DOI: 10.1128/aem.02345-09
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression in Proliferating Cells of the Dinoflagellate Alexandrium catenella (Dinophyceae)

Abstract: Understanding the conditions leading to harmful algal blooms, especially those produced by toxic dinoflagellate species, is important for environmental and health safety. In addition to investigations into the environmental conditions necessary for the formation of toxic blooms, we postulate that investigating gene expression in proliferating cells is essential for understanding bloom dynamics. Expressed sequence tags were produced from cultured cells of the toxic dinoflagellate Alexandrium catenella sampled d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 53 publications
(44 reference statements)
4
50
0
1
Order By: Relevance
“…In the presence of bacteria, the SAM-S and SAHH genes were among the downregulated genes. These genes have been previously reported to be associated with toxin production in dinoflagellates [30,74]. Thus, it seems possible that bacteria may influence toxin production level through these genes.…”
Section: Symbiosismentioning
confidence: 99%
See 2 more Smart Citations
“…In the presence of bacteria, the SAM-S and SAHH genes were among the downregulated genes. These genes have been previously reported to be associated with toxin production in dinoflagellates [30,74]. Thus, it seems possible that bacteria may influence toxin production level through these genes.…”
Section: Symbiosismentioning
confidence: 99%
“…Transcription factors in dinoflagellates are less abundant in comparison to those present in other protists such as Plasmodium, and it has been suggested that this low abundance may be a genomic signature for dinoflagellates [28]. Numerous novel dinoflagellate genes that are involved in gene regulation at the transcriptional and post-transcriptional level have been discovered in the Alexandrium catenella transcriptome, including homologs for a forkhead box protein (FOXL1), multiprotein bridging factor type 1 (MBF1), RAP2.4 and two identified TATA box-binding protein interacting proteins (TBP-IP; RuvB-like 1 and 2) [30]. Interestingly, the genome sequence of Symbiodinium kawagutii possesses a TATA-box binding protein (TBP)-like factor instead of TBP, which has high affinity toward the TTTT promoter motif [15].…”
Section: Dinoflagellates' Growth and Gene Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Both regulation of mRNA abundances (Hosoi-Tanabe et al, 2005;Okamoto and Hastings, 2003;Taroncher-Oldenburg and Anderson, 2000;Toulza et al, 2010) and a high prevalence of translational regulation Lidie, 2007;Rossini et al, 2003) have been reported in dinoflagellates. The discovery of spliced-leader transsplicing (Lidie and Van Dolah, 2007;Slamovits and Keeling, 2008;Zhang et al, 2007) and of single-domain transcripts apparently derived from multi-domain genes led to the suggestion of trypanosome-like mechanisms of spliced-leader-associated constitutive translational gene regulation in dinoflagellates (Monroe and Van Dolah, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Dinoflagellates are important producer of the marine environment because of the large amount of carbon fixed from the photosynthesis [5,6]. These microorganisms are characterized by their reliance towards light intensity since they are exposed to UV light at the pelagic area and rich in chlorophyll contents, which explained the significant of photosynthesis [7].…”
Section: Ecological Importancementioning
confidence: 99%